Kualitas Pengalaman dalam Memoderasi Gaya Hidup, Kesadaran Merek dan Kualitas Rasa terhadap Revisit Konsumen Air Minum Kemasan Aqua - Susi Ari Widiastuti; Surya Bintarti; Musrida Kusuma Wardani (Journal on Education, 2023)
This study aims to find out that lifestyle, brand awareness and taste quality influence consumers' repurchase intentions towards AQUA bottled water products, and also to find out that the quality of experience as a moderation variable can strengthen or weaken. This research uses quantitative methods, where the subject or object of research is people who consume AQUA bottled mineral water in the Bekasi Regency area. On condition, so that this respondent is a proposive sampling. This shows that the population is non-probality so the size of the respondents taken is 80 respondents. The collected data was processed using regression test techniques processed with the SmartPLS 4.0 application. This study concludes: 1) consumers who buy Aqua mineral water products feel that their lifestyle is in accordance with Aqua mineral water products so that consumers consider buying again, 2) brand awareness affects the intention to repurchase Aqua mineral water, it can mean that the more consumers are aware of the brand, the encourage consumers to repurchase, 3) Aqua mineral water products have guaranteed product quality and are safe for consumption thereby encouraging consumers to repurchase again, 4) The quality of experience does not directly affect the consumer's intention to repurchase Aqua mineral water, because of necessity consumer drinking water is not influenced by lifestyle, 5) The quality of direct experience can encourage repurchase intention of consumers of Aqua mineral water, because consumers have personal preferences and previous experience of Aqua mineral water products, 6) The quality of experience can affect consumer repurchase intentions Aqua mineral water, because consumers are satisfied with the quality of Aqua mineral water products which are always maintained.